2012
DOI: 10.1074/jbc.m111.239426
|View full text |Cite
|
Sign up to set email alerts
|

RAD51 Protein ATP Cap Regulates Nucleoprotein Filament Stability

Abstract: Background: RAD51 and RecA homologs form a nucleoprotein filament (NPF) that includes an ATP cap, which sandwiches the adenosine nucleotide. Results: The HsRAD51(D316K) ATP cap substitution dramatically enhances recombinase and NPF stability. Conclusion: The HsRAD51(Asp-316) residue forms a salt bridge with ATP that allows more rapid protein turnover. Significance: HsRAD51(D316K) provides a useful reagent for the study of recombinase function in physiological conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 50 publications
0
38
0
Order By: Relevance
“…Adenosine nucleotide and salt affect the formation of an HsRAD51 NPF on duplex DNA (51). We used buffer conditions in which HsRAD51 bound to the 28-bp dsDNA with or without mismatch in the presence of ADP or ATP yielding slow migrating species in EMSA (52). We found that hMSH2-hMSH6 did not bind to the HsRAD51-coated L28 A/T homoduplex DNA in the presence of ADP (Fig.…”
Section: Hmsh2-hmsh6 Sliding Clamp Is Constrained Within the D-loop Butmentioning
confidence: 99%
See 2 more Smart Citations
“…Adenosine nucleotide and salt affect the formation of an HsRAD51 NPF on duplex DNA (51). We used buffer conditions in which HsRAD51 bound to the 28-bp dsDNA with or without mismatch in the presence of ADP or ATP yielding slow migrating species in EMSA (52). We found that hMSH2-hMSH6 did not bind to the HsRAD51-coated L28 A/T homoduplex DNA in the presence of ADP (Fig.…”
Section: Hmsh2-hmsh6 Sliding Clamp Is Constrained Within the D-loop Butmentioning
confidence: 99%
“…hMSH2-hMSH6, biotinylated hMSH2-hMSH6, HsRPA, and HsRAD51 were expressed and purified as previously described (42,52,66). Cy5-labeled streptavidin was purchased from GE healthcare and purified from excess of unincorporated dye by size exclusion chromatography using a Superdex 200 column.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…HsMSH2-HsMSH6 and HsRPA were purified as previously described (37,38). HsEXOI and HsMLH1-HsPMS2 were purified with modifications to published methods (SI Appendix, SI Methods) (9, 11).…”
Section: Methodsmentioning
confidence: 99%
“…turnover (26). It was more difficult to anticipate the effect of placing an additional negative charge next to this charged aspartate.…”
Section: Significancementioning
confidence: 99%